Local Wisdom in Economic Practice: A Critical Study of Massanra Galung Tradition of the Buginese in Fiqh Muamalah - Mahfudz; Muhammad Ahsanul Amal; Hasniati; Mutmainnah Mustari (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the practice of massanra galung among the Bugis community in Alakaya Village, Southeast Sulawesi, and analyzes its compliance with the principles of fiqh muamalah and maqasid al-shariah. The research integrates legal analysis with socio-cultural perspectives, employing a maqasid al-shariah framework to evaluate the alignment of customary practices with the objectives of Islamic law, namely the protection of hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, and hifz al-mal. Primary data were collected through in-depth interviews with religious leaders, customary authorities, pledgees, and village government officials, complemented by secondary data from relevant literature and documents. Data were analyzed using qualitative descriptive methods, including data reduction, presentation, and conclusion drawing. The findings indicate that massanra galung functions as a trust-based financing mechanism grounded in social solidarity; however, flexibility in repayment terms and the pledgee’s control over rice field yields create asymmetries in bargaining power and risks of economic injustice. Analysis from the perspective of fiqh muamalah and maqasid al-shariah shows that the practice is conditional: it is considered valid and consistent with Shariah objectives if the rights and obligations of all parties are clearly defined, the benefits of the rice field remain with the owner, and the distribution of yields is equitable. The study emphasizes the need to reformulate the practice through written agreements, clear repayment deadlines, fair distribution of yields, and supervision by customary and religious leaders to ensure that the local tradition is preserved while remaining aligned with the principles of Islamic economic justice.